Tumor Necrosis Factor-a Regulates Glucocorticoid Synthesis in the Adrenal Glands of Trypanosoma cruzi Acutely-Infected Mice. The Role of TNF-R1 - Villar, Silvina Raquel (2013)
Adrenal steroidogenesis is under a complex regulation involving extrinsic and intrinsic adrenal factors. TNF-a is an inflammatory cytokine produced in response to tissue injury and several other stimuli. We have previously demonstrated that TNF-R1 knockout (TNF-R12/2) mice have a dysregulated synthesis of glucocorticoids (GCs) during Trypanosoma cruzi acute infection. Since TNF-a may influence GCs production, not only through the hypothalamus-pituitary axis, but also at the adrenal level, we now investigated the role of this cytokine on the adrenal GCs production. Wild type (WT) and TNF-R12/2 mice undergoing acute infection (Tc-WT and Tc-TNF-R12/2 groups), displayed adrenal hyperplasia together with increased GCs levels. Notably, systemic ACTH remained unchanged in Tc-WT and Tc-TNF-R12/2 compared with uninfected mice, suggesting some degree of ACTH-independence of GCs synthesis. TNF-a expression was increased within the adrenal gland from both infected mouse groups, with Tc-WT mice showing an augmented TNF-R1 expression. Tc-WT mice showed increased levels of P-p38 and P-ERK compared to uninfected WT animals, whereas Tc-TNF-R12/2 mice had increased p38 and JNK phosphorylation respect to Tc-WT mice. Strikingly, adrenal NF-kB and AP-1 activation during infection was blunted in Tc-TNF-R12/2 mice. The accumulation of mRNAs for steroidogenic acute regulatory protein and cytochrome P450 were significantly increased in both Tc-WT and Tc-TNF-R12/2 mice; being much more augmented in the latter group, which also had remarkably increased GCs levels. TNF-a emerges as a potent modulator of steroidogenesis in adrenocortical cells during T. cruzi infection in which MAPK pathways, NF-kB and AP-1 seem to play a role in the adrenal synthesis of pro-inflammatory cytokines and enzymes regulating GCs synthesis. These results suggest the existence of an intrinsic immune-adrenal interaction involved in the dysregulated synthesis of GCs during murine Chagas disease.